Global Liberal Education: Contradictory Trends and Heightened Controversy - Boyle, Mary-Ellen (International Higher Education, 2022)
This article defines global liberal education, summarizes global and regional trends, and assesses current key issues including politicization and pandemic impact. It is argued that the waning US influence in global geopolitics has resulted in the acceleration of indigenous efforts as well as innovative approaches to integrating the global and the local.